Creative Economy and Gender Empowerment in Tourism: Investigating Bartender Training for Women in Batu Putih Bawah Village - Pesik, Mex Usmeni; Lagarense, Bet El Silisna; Walansendow, Agustinus; Pangemanan, Jemmy Rudolf; Kondoj, Telly Hetty Isye; Djamali, Radjab; Kamagi, Jongky Wuner; Lumare, Mercy Ariane (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2025)
This study explores the intersection of the creative economy and gender empowerment in the context of rural tourism development. Focusing on bartender training for women in Batu Putih Bawah Village, Bitung City, Indonesia, the research investigates how vocational skill development in mixology can serve as a strategic entry point for women's participation in the tourism value chain. Drawing from a gender-inclusive development framework and the creative economy paradigm, the study employs a qualitative case study method involving interviews, observations, and documentation. The findings suggest that bartender training not only enhances women's technical competencies but also fosters self-confidence, economic independence, and social recognition. However, structural challenges such as limited market access, traditional gender roles, and a lack of institutional support remain persistent barriers. This research contributes to the discourse on sustainable tourism and inclusive growth by proposing an integrated model for women’s empowerment through creative vocational pathways. The study also provides insights for policymakers, tourism practitioners, and educators seeking to strengthen local capacities and gender equity within emerging tourism destinations.